2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626392
|View full text |Cite
|
Sign up to set email alerts
|

Arousing feedback rectifies lapse in performance and corresponding EEG power spectrum

Abstract: This study explores electroencephalographic (EEG) dynamics and behavioral changes in response to arousing auditory signals presented to individuals experiencing momentary cognitive lapses. Arousing auditory feedback was delivered to the subjects in half of the non-responded lane-deviation events during a sustained-attention driving task, which immediately agitated subject's responses to the events. The improved behavioral performance was accompanied by concurrent power suppression in the theta- and alpha-bands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It seems that negative feedback leading to external error detection itself results in the enhancement of attention. Other studies also demonstrated an effect of negative feedback-related alpha suppression and interprete it as enhanced arousal, alertness and attention induced by external error detection (Papo et al, 2007; Jung et al, 2010; Luft et al, 2014). …”
Section: Discussionmentioning
confidence: 96%
“…It seems that negative feedback leading to external error detection itself results in the enhancement of attention. Other studies also demonstrated an effect of negative feedback-related alpha suppression and interprete it as enhanced arousal, alertness and attention induced by external error detection (Papo et al, 2007; Jung et al, 2010; Luft et al, 2014). …”
Section: Discussionmentioning
confidence: 96%
“…However, the study also showed that auditory feedback sometimes failed to arouse drowsy subjects and that the EEG activity of these non-responsive episodes showed no neural response to the feedback (Lin et al 2010. A pilot study (Jung et al 2010) applied machine-learning algorithms to assess the efficacy of the arousing feedback on drowsy subjects and showed that the post-stimulus EEG spectra could be used to estimate the effectiveness of the arousing signals with a moderate accuracy of 61%.…”
Section: Introductionmentioning
confidence: 99%